(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
On the territory of siх working oil wells of Boryslav, species composition and ecological preferences of mosses is analysed. Morpho-physiological variability of Ceratodon purpureus and its oil pollution tolerance features is investigated experimentally.